The Impact of Interoceptive Awareness on Pain Catastrophizing and Illness Perception - Hooshmandi, Roodi; Aljaberi, Musheer Abdulwahid; Hammadi, Fethi; Ma, James (Journal of Personality and Psychosomatic Research (JPPR), 2024)
This study aimed to investigate the effectiveness of Interoceptive Awareness Training (IAT) in reducing pain catastrophizing and altering illness perceptions among individuals with chronic pain. It sought to determine whether enhancing interoceptive awareness could lead to improved management and perception of chronic pain. Employing a randomized controlled trial design, 30 participants with chronic pain were assigned to either an intervention group, receiving 10 sessions of IAT, or a control group receiving standard care. Measurements of pain catastrophizing and illness perception were taken at baseline, immediately post-intervention, and at a three-month follow-up, utilizing the Pain Catastrophizing Scale (PCS) and the Illness Perception Questionnaire-Revised (IPQ-R), respectively. Participants in the intervention group demonstrated significant reductions in pain catastrophizing scores from baseline to follow-up, as well as significant improvements in illness perception scores. These changes indicate a substantial shift in how participants understood and reacted to their pain post-intervention compared to the control group, which showed no significant alterations in either pain catastrophizing or illness perception. Interoceptive Awareness Training significantly reduced pain catastrophizing and positively altered illness perceptions in individuals with chronic pain. The findings suggest that IAT can be an effective component of comprehensive pain management strategies, highlighting the importance of addressing the psychological dimensions of chronic pain in conjunction with physical treatment modalities.